Generating dual structurally and functionally skin-mimicking hydrogels by crosslinking cell-membrane compartments - Feng Wu; Yusheng Ren; Wenyan Lv; Xiaobing Liu; Xinyue Wang; Chuhan Wang; Zhenping Cao; Jinyao Liu; Jie Wei; Yan Pang (Nature Communications, 2024)
Abstract The skin is intrinsically a cell-membrane-compartmentalized hydrogel with high mechanical strength, potent antimicrobial ability, and robust immunological competence, which provide multiple protective effects to the body. Methods capable of preparing hydrogels that can simultaneously mimic the structure and function of the skin are highly desirable but have been proven to be a challenge. Here, dual structurally and functionally skin-mimicking hydrogels are generated by crosslinking cell-membrane compartments. The crosslinked network is formed via free radical polymerization using olefinic double bond-functionalized extracellular vesicles as a crosslinker. Due to the dissipation of stretching energy mediated by vesicular deformation, the obtained compartment-crosslinked network shows enhanced mechanical strength compared to hydrogels crosslinked by regular divinyl monomers. Biomimetic hydrogels also exhibit specific antibacterial activity and adequate ability to promote the maturation and activation of dendritic cells given the existence of numerous extracellular vesicle-associated bioactive substances. In addition, the versatility of this approach to tune both the structure and function of the resulting hydrogels is demonstrated through introducing a second network by catalyst-free click reaction-mediated crosslinking between alkyne-double-ended polymers and azido-decorated extracellular vesicles. This study provides a platform to develop dual structure- and function-controllable skin-inspired biomaterials.